MURABAHAH FINANCING ON NON-PERFORMING FINANCE IN SHARIA COMMERCIAL BANKS IN INDONESIA - Ramadhani, Kiki Yulia Nurul; Marchase, Malvina; Verliani Dasmaran (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
The purpose of this study is to find out how Murabahah Financing affects Non-Performing Finance (NPF) at Islamic Commercial Banks in Indonesia from 2018 to 2021. The research method was carried out using a quantitative method using secondary data. Secondary data is taken from the Sharia Banking Statistics report published by the Financial Services Authority (OJK) of Bank Indonesia for the period January 2018 to December 2021. There are 48 data in this research. The dependent variabel in this study is Murabahah Financing, while the dependent variabel is NPF. The analysis technique uses regression analysis, correlation and determination using the SPSS 23 application. The results of the enter method regression analysis yielded a correlation (R) of 0.701 and a coefficient of determination (R square) of 0.491 and the ANOVA results of F count regression 44.403 with a significance of 0.000<0.05. So it can be concluded that Murabaha financing has a negative effect on NPF.